Mitochondria-associated endoplasmic reticulum membranes (MAMs): Possible therapeutic targets in heart failure - Zhang, Yu; Yao, Jiayu; Zhang, Mingming; Wang, Yushan; Shi, Xingjuan (Frontiers in Cardiovascular Medicine, 2023)
Mitochondria-associated endoplasmic reticulum membranes (MAMs) are formed by physical connections of the endoplasmic reticulum and mitochondria. Over the past decades, great breakthroughs have been made in the study of ER-mitochondria communications. It has been identified that MAM compartments are pivotal in regulating neurological function. Accumulating studies indicated that MAMs participate in the development of cardiovascular diseases. However, the specific role of MAMs in heart failure remains to be fully understood. In this paper, we first summarize the structural and functional properties of MAM and MAM-associated proteins. We then focus on the roles of MAMs in myocardial infarction, cardiomyopathy and heart failure, and discuss the involvment of MAMs in disease progression and treatment. Elucidating these issues may provide important insights into therapeutic intervention of heart failure.